Building Consumer Loyalty: The Role of Product Quality and Price in Purchase Decisions of Brand Executive in South Tangerang - Harianja, Tombang Daulat Ni Roha (Baileo: Jurnal Sosial Humaniora, 2025)
This study aims to analyze the influence of product quality and price on the purchase decisions of Brand Executive in South Tangerang. In an increasingly competitive digital era, understanding the key factors affecting consumer behavior is essential for business sustainability in the fashion industry. Using a quantitative method, data were collected through questionnaires distributed to 140 respondents. Regression analysis showed that product quality had a significant influence on purchase decisions, with a regression coefficient of 0,56, a t-value of 5,783 (greater than the t-table value of 1,660), and a significance value of 0,000 (< 0,05). In contrast, price did not have a significant effect on purchase decisions, with a regression coefficient of 0,149, a t-value of 1,247 (lower than the t-table value), and a significance value of 0,214 (> 0,05). These results indicate that consumer perception of product quality is the dominant factor in purchase decision-making, whereas price is not a primary determinant in the competitive fashion market, especially in e-commerce ecosystems such as TikTok Shop. The novelty of this study lies in exploring the role of price in the dynamics of the digital fashion market, showing that product differentiation based on quality has a greater impact than pricing strategies. These findings provide recommendations for Brand Executive managers to prioritize product quality innovation to enhance consumer loyalty. Academically, this study contributes to consumer behavior research in the fashion industry and enriches social sciences and humanities studies related to consumer value-based marketing strategies.